Building Tax Awareness from an Early Age: Outreach to Elementary Schools in Serang, Banten - Noorida Soerono, Ayu; Nurhayati, Enok; Adiwijaya, Edwin Perdana (EQUATOR SINAR AKADEMIA, 2025)
Taxes are a state's primary revenue source and are crucial to national development. However, public awareness of the importance of taxes remains low among the younger generation. Therefore, early tax education is essential to understand and be aware of tax obligations. This article discusses a community service activity in the form of tax socialization for elementary school students in Serang, Banten, using an interactive and engaging approach. The methods include short lectures, educational games, and simple tax-related simulations. Evaluation results demonstrate an improvement in students' understanding of tax concepts and their benefits for development. This initiative is expected to serve as an initial step in building early tax awareness and encouraging active participation of the younger generation in contributing to national development.